Do the effects of organizational trust on correctional staff job attitudes vary by culture: A preliminary test with Nigerian prison staff. Issue 1 (11th May 2022) - Lambert, Eric G.; Elechi, O. Oko; Baker, David; Jenkins, Morris; Otu, Smart; Lanterman, Jennifer L.
Abstract: The current study explored the effects of coworker, supervisor, and management trust on the job involvement, job satisfaction, and organizational commitment of Nigerian prison staff working in a prison in southeast Nigeria. In multivariate regression, only management trust was a significant positive predictor of job involvement. Supervisor and management trust, but not coworker trust, had significant positive associations with organizational commitment. All three dimensions of organizational trust had significant positive relationships with job satisfaction. These results suggest that both supervisory and management trust are important to correctional officers in Nigeria, which are similar to empirical research studies in the United States. The effects of trust may be universal among correctional staff across different cultures.